RNAi screening in glioma stem-like cells identifies PFKFB4 as a key molecule important for cancer cell survival - Goidts, Violaine; Bageritz, Josephine; Zapatka, Marc; Tödt, Grischa; Campos, Benito; Korshunov, Andrey; Herold-Mende, Christel; Lichter, Peter; Radlwimmer, Bernhard (Oncogene, 2012)
The concept of cancer stem-like cells (CSCs) has gained considerable attention in various solid tumors including glioblastoma, the most common primary brain tumor. This sub-population of tumor cells has been intensively investigated and their role in therapy resistance as well as tumor recurrence has been demonstrated. In that respect, development of therapeutic strategies that target CSCs (and possibly also the tumor bulk) appears a promising approach in patients suffering from primary brain tumors. In the present study, we utilized RNA interference (RNAi) to screen the complete human kinome and phosphatome (682 and 180 targets, respectively) in order to identify genes and pathways relevant for the survival of brain CSCs and thereby potential therapeutical targets for glioblastoma. We report of 46 putative candidates including known survival-related kinases and phosphatases. Interestingly, a number of genes identified are involved in metabolism, especially glycolysis, such as PDK1 and PKM2 and, most prominently PFKFB4. In vitro studies confirmed an essential role of PFKFB4 in the maintenance of brain CSCs. Furthermore, high PFKFB4 expression was associated with shorter survival of primary glioblastoma patients. Our findings support the importance of the glycolytic pathway in the maintenance of malignant glioma cells and brain CSCs and imply tumor metabolism as a promising therapeutic target in glioblastoma.
Published online 7 November 2011
Gesehen am 06.12.2018